NANOPARTICULATE BDNF AS A POTENTIAL ANTIDEPRESSANT VIA NEUROENDOCRINE MECHANISMS IN EXPERIMENTAL MODEL OF DEPRESSION - N.A.D. BINTI RAZLAN; M. KAPITONOVA; S.B. TALIP; N. RAMLI; I.B. BROHI; T.M. NWE; R.N. ALYAUTDIN; R.N. ALYAUTDIN (Avicenna Tajik State Medical University, 2024)
Objective: To study the effect of a nanoparticulate brain-derived neurotrophic factor with surfactant (BDNF) on the modeled depression not associated with stress in mice Methods: Thirty-six C57BL/6 mice weighing 20-25 g were included in the study with reserpine-induced depression. The animals were divided into three groups: Group 1 - negative control, involving animals treated with normal saline, Group 2 - positive control involving animals treated with a traditional antidepressant fluoxetine, and Group 3 - experimental, treated with nanoparticulate BDNF with a surfactant. Open field, sucrose preference, and forced swimming tests were applied in the study, and the ELISA method was used to determine the corticosterone level in the serum. Digital morphometry of the adrenal cortex and thymus was done. SPSS 27.0.1 software was used for statistics, with a p<0.05 level of significance Results: The mice of the BDNF and fluoxetine groups exhibited meaningfully lower levels of serum corticosterone (p<0.01), and considerable improvements in the open field, sucrose preference, and forced swimming tests (p<0.01) than the animals of the normal saline group. Digital morphometry showed a meaningful reduction in the share of the zona fasciculata in the adrenal gland, the area of its cells, and their nuclei in the BDNF group compared to the animals treated with normal saline (p<0.05). In contrast, the difference between the fluoxetine and normal saline groups was insignificant. A meaningfully higher thymic cortex-medulla ratio was noted in the mice of the BDNF group compared to the normal saline (p<0.01) and fluoxetine (p<0.05) groups, and a lower percentage of macrophages with apoptotic bodies compared to normal saline (p<0.01) and fluoxetine groups (p<0.05), which was not significantly different between the fluoxetine and normal saline groups. Conclusion: Nanoparticulate BDNF with a surfactant shows the efficacy of treatment of modeled depression comparable with the traditional antidepressant fluoxetine, as evidenced by behavioral tests, decreased corticosterone levels, or even exceeding it, as shown by significantly reduced hyperplasia of the zona fasciculata of the adrenal gland and of its cells, as well as reduced immunosuppressive changes in the thymus (higher corticomedullary ratio, lower volume density of the tingible body macrophages). These results underscore the potential of nanoparticulate BDNF as a treatment for depression not associated with stress.